Eurozone: die Krise als Chance für die kapitalistische Offensive - Milios, Jannis; Sotiropoulos, Dimitris (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
The article criticizes the usual narrative, that the indebtedness of the southern countries of EU is the result of reckless borrowing, exaggerated consumption and productive weakness. It is shown how current account imbalances worked for some years as an accommodation process. However, the Euro is not just a currency, it is a “mechanism” to impose capitalist power, to force permanent processes of restructuring labour. The contemporary crisis of the Euro is not just the outcome of a wrong policy, it is a process of capitalist attack in class struggle.